THE IMPACT OF EXPLICIT LINGUOPRAGMATIC INSTRUCTION ON ENGLISH LANGUAGE LEARNERS IN ELT - Khalifa Paluanova (Western European Studies, 2024)
This study investigates the transformative effects of explicit linguopragmatic instruction on the communicative competence of English language learners (ELLs) within English Language Teaching (ELT). Employing rigorous quantitative analysis and thematic interviews with experienced teachers, the research reveals significant improvements in ELLs’ understanding and application of linguopragmatic concepts, particularly in politeness strategies and implicature. Findings underscore the broader impact beyond speech acts, aligning with contemporary pedagogical challenges. Despite challenges such as limited curriculum time, the study advocates for pedagogical strategies emphasizing pragmatic competence. This research contributes to the discourse on linguopragmatics, emphasizing its practical applicability in fostering effective and culturally sensitive communication
Keywords: linguopragmatics; communicative competence; English Language Teaching